FAKTOR-FAKTOR YANG MEMENGARUHI BRAND LOYALTY PENGGUNA LAPTOP ASUS DI KOTA BEKASI - WILLY, WILLY; SUTRISNO, NUNO (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
This research was conducted with the aim of finding out the influence of Satisfaction, Trust, Inertia, and Commitment on Brand Loyalty among Asus laptop users in Bekasi City. The data collection technique used in this research is a survey, where data analysis uses quantitative research using a causal research design. The sampling method is non-probability sampling, with purposive sampling technique. Where a five-point Likert scale is used for each measurement. This study uses primer data, with 140 responses to the total sample collected by distributing questionnaires using SPSS 25 (Statistical Program for Social Science). The analysis of data method used is multiple linear regression. It is hoped that this research can provide input to IT companies, especially Asus, which is the object of this research, so that they can increase their market share in the IT industry in Indonesia.